Mediasi Media Massa Menuju Nilai-nilai Baru dalam Pendidikan Tinggi Indonesia: Sebuah Tinjauan Ekonomi Pengetahuan - Fit Yanuar; Daesy Ekayanthi; Titi Widaningsih; Udi Rusadi (Universitas Indraprasta PGRI Jakarta, 2023)
In April 2023 there was disorder in the world of Indonesian higher education when the Indonesian Ministry of Education and Culture asked Indonesian lecturers to fill in credit scores in an information system. The pressed deadline and protracted lecturer administration issues have led to resistance from lecturers in April 2023, which was responded by cancelling the policy by the Indonesian Ministry of Education and Culture. This phenomenon is interesting to study using the theory of hyper-capitalism and the knowledge economy of Philip W. Graham, a philosopher based on media-political-economy studies. In his series of theories, Graham spawned a method of analysis which he called discourse historical in which communication, language, and the mass media play a role in a mediation process that will produce new values. As a result of the research it can be shown that the mass media has been used and has a major role in the mediation process related to the Indonesian-style knowledge economy to create new values. However, a question remains whether the Indonesian Ministry of Education and Culture will produce a teaching administration policy that will truly make it easier for Indonesian lecturers to work in education, and so on, will make the dynamics of Indonesian education even better.